2021
DOI: 10.21037/apm-21-410
|View full text |Cite
|
Sign up to set email alerts
|

The incidence, risk factors, and prognosis of postoperative hyperbilirubinemia after cardiac surgery: a systematic review and meta-analysis

Abstract: Background: The purpose of the present systematic review was to evaluate the incidence, risk factors, and outcome of hyperbilirubinemia after cardiac surgery.Methods: The Population, Interventions, Comparators, Outcomes, and Study design (PICOS) framework was employed to develop the search strategy, and the findings are reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. PubMed, Embase, and the Cochrane Library were systematically searched for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…The establishment of the CPB circuit will also increase the production of reactive oxygen species and inflammatory factors and induce acute tubular necrosis. In addition, hyperbilirubinemia after cardiac surgery with CPB is frequently observed and associated with worse outcomes (27). A large prospective study found a positive association between hyperbilirubinemia and the incidence of AKI after CPB (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The establishment of the CPB circuit will also increase the production of reactive oxygen species and inflammatory factors and induce acute tubular necrosis. In addition, hyperbilirubinemia after cardiac surgery with CPB is frequently observed and associated with worse outcomes (27). A large prospective study found a positive association between hyperbilirubinemia and the incidence of AKI after CPB (28).…”
Section: Discussionmentioning
confidence: 99%
“…Our study reveals that a postoperative TBIL ≥60 umol/L is an independent risk factor for requiring RRT after HT (OR =5.105; 95% CI: 1.868-13.952; P=0.001). Though the exact cause of this liver dysfunction is unknown, it may be secondary to liver hypoperfusion, hemolysis or a systemic inflammatory response to CPB (27).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperbilirubinemia is a common complication that occurs after cardiac surgery due to hemolysis and/or liver hypoperfusion, especially under cardiopulmonary bypass (CPB) ( Collins et al, 1983 ; Wang et al, 1994 ). Previous studies indicated that the incidence of postoperative hyperbilirubinemia (PH) ranged from 10% to 40% in cardiac surgery and associated with increased postoperative morbidity and mortality ( Nishi et al, 2012 ; Yang et al, 2019 ; Chen et al, 2021 ). However, the clinical significance of PH after surgical repair of ATAAD has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Jaundice due to hyperbilirubinemia develops in 10-23% of patients in the early period after cardiac surgery. [1,2] Despite advances in surgical techniques and post-operative patient care, the incidence of hyperbilirubinemia does not appear to have decreased compared to studies 40 years ago. [3] Increasing and severe hyperbilirubinemia occurring in the late post-operative days was associated with higher mortality and morbidity than mild hyperbilirubinemia occurring in the 1 st days.…”
Section: Introductionmentioning
confidence: 99%